The impact of socialised conflict management techniques within a law firm in Port Elizabeth - Pretorius, Dewald (The IIE, 2020)
The behaviour and values that we acquire from our culture can impact how we perform within the workplace setting (de Swardt, van Rensburg & Oosthuizen, 2017). Probably one of the most important factors to deal with in a culturally diverse workforce is conflict. Different cultures learn different ways of handling conflict; however, culture is not only limited to ethnic background. Organisations often socialise their employees to follow the organisational culture. As such the aim of the study was to determine the impact of socialised conflict management techniques within a law firm within Port Elizabeth. The research was qualitative in nature and followed the interpretive paradigm. Data was collected through means of Skype interviews as the COVID-19 pandemic prevented face-to-face interviews to be done in person. The data analysis process involved content analysis of the interview transcripts. Three theories were utilised for this study: Thomas-Kilmann’s Interpersonal conflict theory, Galtung’s conflict triangle and Albert Banduras social learning theory. The study revealed that the law firm’s workplace culture was the main factor influencing socialised conflict management techniques as opposed to ethnic cultural background.
Keywords: Socialisation; Conflict management techniques; Law firms